Reflective teaching practice in a remote teaching context by COVID-19 - Rojas Romero, Karin Corina (2022)
In Peru, the coronavirus disease pandemic (COVID-19) has generated an unprecedented crisis in all areas. In the educational sector, this health emergency has caused the massive closure of face-to-face activities in public and private educational institutions, teachers and students have had to reinvent themselves to continue with the teaching-learning process. The objective of this research was to describe the level of reflection of teachers on their practice in a distance learning context using Covid-19. This research was quantitative, descriptive and cross-sectional. A sample of 300 teachers was taken. Of the three levels with 100 teachers each, some levels stand out with a higher percentage in the reflection processes by dimensions. In conclusion, the comparative result between the initial, primary and secondary levels of RED 7, the jurisdiction of UGEL 05 on the process of reflection on the pedagogical practice of teachers in the context of distance learning by Covid-19 describes that 84% of the NI execute it always; 74% of the NP, 76% of the NS and 25% execute it almost always.